Sistemática das espécies de cascudos “acari-cachimbo” do gênero Hemiodontichthys bleeker, 1862 (Siluriformes: Loricariidae) com a descrição de quatro espécies novas - MENDONÇA, Marina Barreira (Universidade Federal do Pará, 2013)
The taxonomic revision of the genus Hemiodontichthys Bleeker, 1862 resulted in the recognition of five valid species, including four new species. A new diagnosis for the genus is provided, H. acipenserinus is redescribed, an identification key is included, and a distribution map for the genus is provided. Hemiodontichthys sp. “Coari” occurs in the Urucu basin, Hemiodontichthys sp. “Tocantins” in the Tocantins drainages, Hemiodontichthys sp. “Peru1” in the Madre de Dios , Ucayali and Nanay rivers, on Peru, Hemiodontichthys sp. “Peru2” has an inaccurate location on Iquitos, and the type-species H. acipenserinus, occurs on Guaporé river, Madeira river, and in the middle and lower Amazon river. Comments about the monophyly of Hemiodonthichthys are presented.